Understanding the Challenges Faced by Fish Vendors in Iriga City Public Market - Cristina C. Bermas; Estelita M. Canuto; Dandy B. Centillas; Jercy S. Orante; Cherry E. Peña (Journal of Management Studies and Development, 2023)
This study aimed to determine the factors affecting the profitability of fish vendors in Iriga City Public Market. The researchers identified the profile of the respondents in terms of gender, age, civil status, family income, and years of doing business. They also determined the factors affecting profitability in terms of product, price, demand, supply, and competition. Findings showed that most fish vendors were female, aged 41-50 years old, married, and had a weekly family income of Php. 500-Php. 1,000. Some vendors had been in business for 10 years, while others were just starting. The product in the market met the needs of customers, while the price was practical and affected by inflation. Demand for fish products was met, and supply was able to keep up with customer demand. Competition was also a factor. The researchers proposed programs to enhance the financial management of fish vendors. The study concluded that the factors affecting profitability were the product offered, price, demand and supply, and competition. The proposed programs could help fish vendors address challenges that affect their profitability. The study recommended that fish vendors should be knowledgeable in pricing strategies, demand and supply factors, and fair competition.